Physical aspects of photodinamic therapy application to chronic vulvovaginal candidiasis - K O Aslanyan; I A Apolikhona; T A Teterina; M N Kholodtsova (IP Berlin A.V., 2014)
The aim of the presented research was investigation of induced by 5-ALA PPIX accumulation kinetics in mucosa, vagina and vulva chronic in women with vulvovaginal candidiasis after treatment of 5-ALA and the choice of optimal time mode of fluorescence diagnosis and photodynamic therapy (PDT) in chronic vulvovaginal candidiasis. The investigation was held in group of 60 women: 20 with vulvovaginal candidiasis, 25 - bacterial vaginosis, 15 - non - specific vaginitis. Each woman had 4 sessions of PDT. Before and after each of the sessions fluorescence diagnosis (FD) of photosensitizer accumulated in mucosa, vagina and vulva was performed. By means of local fluorescent spectroscopy difference of accumulated PPIX was estimated with statistical methods. It was obtained, that difference between accumulation of PPIX after 1, 2, 3 and 4th session is statistically significant. After the 4th session it was estimated that there is no significant statistical difference between PPIX accumulated in healthy tissue and mucosa of vagina. According to this we concluded, that PDT in this case showed high efficiency.